Dithienocoronene diimide (DTCDI)-derived triads for high-performance air-stable, solution-processed balanced ambipolar organic field-effect transistors. Issue 30 (27th July 2021) - Ran, Huijuan; Li, Fei; Zheng, Rong; Ni, Wenjing; Lei, Zheng; Xie, Fuli; Duan, Xuewei; Han, Ruijun; Pan, Na; Hu, Jian-Yong
Abstract : Three end-capping π-conjugated DTCDI-based triads and their applications in high-performance, air-stable, solution-processed, balanced ambipolar OFETs are reported. Abstract : Developing ambipolar organic semiconducting materials is essential for use in complementary-like inverters and light-emitting transistors. In this study, three new dithienocoronenediimide (DTCDI)-derived triads, DTCDI-BT, DTCDI-BBT and DTCDI-BNT, were designed and synthesized, in which various sizes of terminal groups, i.e., thiophene (T), benzo[ b ]thiophene (BT) and naphtha[2, 3- b ]thiophene (NT) were substituted at the α-positions of the two thiophene rings of DTCDI, respectively. The DFT calculations reveal that the HOMO energy levels of the three triads when compared to that of the parent DTCDI-core (−5.99 eV) are significantly increased to −5.59, −5.59 and −5.45 eV for DTCDI-BT, DTCDI-BBT and DTCDI-BNT, respectively, whereas the LUMO energy levels (−3.07 eV ∼ −3.14 eV) are almost identical with that of the DTCDI-core (−3.10 eV). The results predict that the triads could possess ambipolar transport properties in organic field-effect transistor (OFET) applications. In fact, under an ambient atmosphere, solution-processed bottom-gate top-contact (BGTC) transistors exhibit ambipolar charge transport properties by tuning the HOMOs of the DTCDI-based triads so that they were suitable for hole injection, resulting in balanced maximum electron and hole mobilities of 1.66 × 10 −3 and 1.02 × 10 −3 cm 2 V −1 s −1 for DTCDI-BT, 2.60 × 10 −2 and 3.60 × 10 −2 cm 2 V −1 s −1 for DTCDI-BBT, and 2.43 × 10 −3 and 4.15 × 10 −3 cm 2 V −1 s −1 for DTCDI-BNT, respectively. This is the first time that the DTCDI building block has been used to develop ambipolar small molecular semiconductors, and achieved a device performance comparable to that of the DTCDI-based polymeric semiconductors. In addition, DTCDI-BBT -based complementary-like inverters were made, and the inverter devices operated well in both p-mode and n-mode under ambient conditions. The results show that the DTCDI is a promising π-electron-deficient building block which could be further used to develop ambipolar semiconducting materials for OFET devices.